#selfie: digital self-portraits as commodity form and consumption practice. Issue 5 (2nd September 2016) - Iqani, Mehita; Schroeder, Jonathan E.
ABSTRACT: Although selfies may appear to be the latest fad, their popularity has had a transformational influence on contemporary culture. Selfies invoke important issues in communication, photography, psychology, self-expression, and digital media studies – as they bring up a host of concerns about identity, privacy, security, and surveillance. This article provides an interdisciplinary overview of the selfie as both an object and a practice, and offers theoretical reflections on how the selfie can be seen as an important commodity form and consumer behaviour. The selfie is connected to concepts of authenticity, consumption, and self-expression, as well as practices of art history, media forms, and self-portraiture. Strategic use of the selfie reveals shifts in the traditional functions of the advertising photograph, from sources of information, persuasion, and representation to emblems of social currency. We position the selfie not as a postmodern anomaly but as a type of image with a history.